Anal cancer in people living with HIV: A case series. (January 2020) - Sadlier, Corinna; Lynam, Almida; Kerr, Colm; Sheils, Orla; Bergin, Colm
Human papillomavirus (HPV) causes almost 5% of all cancers worldwide including cervical cancer, oropharyngeal cancers, vulval cancer, penile cancer and anal cancer. HPV-associated anal squamous cell carcinoma is a rare occurrence in the general population; however, the incidence is increasing. Certain groups including people living with HIV are disproportionately affected. In this case series, we report baseline demographics, clinical characteristics and outcome of anal cancer cases presenting in people living with HIV over a ten-year period (2006–2015).